CASH HOLDING, UMUR PERUSAHAAN DAN STRATEGI BISNIS SEBAGAI FAKTOR PENDORONG INCOME SMOOTHING - Widodo, Wahyudi; Redonoarsi, Rarasasi Ribka; Ardianto, Dedi; Wulandari, Arum; Nofryanti, Nofryanti (Jurnal Riset Terapan Akuntansi, 2024)
The importance of profit disclosure becomes one of the reasons why management carries out dysfunctional behaviors, by carrying out income smoothing to overcome conflicts of interest arising between management and stakeholders. One of the motives for the income smoothing is grabbing that intended to minimize fluctuations in profits so that it appears stable. The purpose of this study is to ascertain how cash holding, firm age, and business strategy affect the incentive to engage in income smoothing. The four-year period covered in the study was 2019–2022. All consumer products companies that were listed at the same time on the Indonesia Stock Exchange (BEI) are included in the population. Secondary data from the company's official website and the Indonesian Stock Exchange website were used. The purposive sampling strategy is used in this study. 33 firms were obtained based on the defined parameters. Panel data logistic regression analysis is the analytical technique employed. The findings indicate that while company age has little bearing on income smoothing, cash on hand does. Meanwhile, business strategy, which is proxied by EMP/Sales, MtoB, Market, and PPEINT, though partially shows different results, however, they simultaneously influence on income smoothing practice. Therefore, the three mentioned variables are worthed to become investors’ concerns to keep from bias understanding of financial reporting of an entity. Keywords: Income Smoothing, Cash Holding, Firm Age, Business Strategy